The Analysis of Eating Habits of Hyperuricemia Sufferers in Padang City - Cesar Welya Refdi; Rina Yenrina; Kesuma Sayuti; PY Fajri (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2020)
Hyperuricemia is a condition when uric acid levels in the blood are higher than normal. It can lead to several diseases, like gout. The data from the Health Office of Padang City in 2013-2015 show that gout is included in the category of 10 most diseases in Padang City. The typical foods of West Sumatera contain high-protein. This may correlate with the increase in the number of hyperuricemia sufferers in Padang City, West Sumatera. The aim of this study is to know the eating habits of hyperuricemia sufferers in Padang City. This research method was explorative-descriptive using a survey conducted on respondents of hyperuricemia sufferers. The respondents surveyed were thirty-seven people, randomly assigned to the patients of health facilities in Padang City. The results indicated that hyperuricemia sufferers are under and above 40 years old. Animal source foods stated by respondents that can increase uric acid were tunjang, cancang, and beef liver. Meanwhile, plant source foods stated by respondents that can increase uric acid were legumes (melinjo/emping, tauco, dan gado-gado/lotek/pical), leafy greens (cassava leaf, spinach, and kale) and fruits (durian, jack fruit, and banana). Ginger, red ginger, and garlic are believed by the respondents to reduce gout.